Optimalisasi Tebal Perkerasan Pada Pekerjaan Pelebaran Jalan dengan Metode MDPJ 02/M/BM/2013 dan Pt T-01-2002-B - Andriansyah, Andriansyah; Pratomo, Priyo; Ali, Hadi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
Every year, goverment incur huge cost for development of facilities and infrastructures oftransportation, especially land transportation development by increasing the road capacity. Thiscapacity expansion is done by widening the road, especially on roads that can no longeraccommodate the volume of vehicles or roads that predicted will be passed by the high volume ofvehicles. Therefore, it is required pavement thickness design solutions that based on a life cyclecost analysis and the lowest consideration of construction resources to the minimum life cycle costdesign.This research was conducted in A. H. Nasution Street, on Metro - Gedung Dalam segment. Todetermine the flexible pavement thickness, this research uses “Manual Desain Perkerasan Jalan02/M/BM/2013”, “Pedoman Perencanaan Tebal Perkerasan Lentur Pt T-01-2002-B” and“Perencanaan Tebal Perkerasan Lentur Jalan Raya dengan Metode Analisa Komponen 387-KPTS-1987 methods”. After that, analyze the road deterioration that will happen during the lifedesign or life cycle design that based on the value of IRI. The results of life cycle design wasdeveloped to get the best pavement type that based on the life cycle cost analysis.From the analysis that has been done, the design with the lowest initial cost is a pavement designby using Bina Marga Pt-T-01-2002-B method, whereas the design with the lowest life cycle cost isa pavement design by using MDPJ 02/M/BM/2013 method and the most optimal pavementthickness.Keywords : flexible pavement, life cycle cost, life cycle design, IRI